Optimasi Formulasi Ayam Petelur Menggunakan Metode Pemrograman Linier untuk Meminimalkan Biaya Pakan pada BUMDes Maju Bersama Lengkiti - Azhari, Yoga; Handoko, Doddy; Risalman, Nurmulia Risky; Muslim, Edi; Destiarini, Destiarini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Feed costs are the largest component in laying hen production, which can reach 70% of the total cost, so an efficient formulation is needed to maintain profitability. This study aims to optimize laying hen feed formulations using linear programming methods to minimize feed costs without reducing nutritional adequacy. A quantitative approach was used by developing a linear programming model that considers the essential nutrient requirements such as protein, energy, calcium, and phosphorus, with feed ingredients including corn, soybean meal, bran, fish meal, and limestone. The optimization process was carried out with the help of computational tools to determine the lowest-cost combination of feed ingredients that still meets the nutritional standards of laying hens. The research results indicate that the optimized formulation successfully reduced feed costs compared to conventional formulations without compromising nutritional quality. In addition, this model also provides flexibility in substituting feed ingredients when market price fluctuations occur, allowing farmers to adjust to dynamic economic conditions. In conclusion, the linear programming method has been proven effective in formulating cost-effective layer chicken feed, offering financial benefits as well as practical applications in the poultry farming sector.